P223a Increasing the quality of COPD case finding, diagnosis and management through a primary care financial incentive scheme in inner London. (2nd December 2011) - Contreras, M Calonge; Billett, J; Restrick, L; Sennett, K; Cooper, C; Stern, M
Abstract : Introduction and Objectives: COPD is a major cause of mortality/morbidity in high smoking prevalence Primary Care Trusts (PCTs). Our PCT expected COPD prevalence (3.7%) is therefore high but recorded prevalence (2009/2010) was 1.4%, suggesting large numbers of undiagnosed patients. COPD, as the 2nd commonest cause of emergency admission locally, is one of the most costly diseases for secondary care. Local research (Bastin et al, 20101 ) shows that, while most patients admitted for the first time with acute exacerbations of COPD have severe disease, there is no prior diagnosis in ∼1/3 cases. A COPD Local Enhanced Service (LES) was developed, to incentivise practices to proactively identify, diagnose and manage COPD patients using evidence-based interventions. Methods: All GP practices in were invited to participate in the COPD LES. Key elements included number of case finding spirometries performed in smokers/ex-smokers =35 y, and provision of interventions (pulmonary rehabilitation (PR) referral, self-management, oxygen auditing) with regular reviews/assessments. Primary outcomes were the number of new COPD diagnoses, a change in the gap between recorded and estimated COPD prevalence and number of non-elective hospital admissions. Data were extracted from the PCT GP dataset, QMAS (diagnosed prevalence), APHO COPD-prevalence model (expected prevalence) and Secondary Users Services (hospital admission data). Results: 37/38 (97%) GP practices signed up to provide the LES. Between April 2010 and May 2011, 1807 case finding spirometries were performed resulting in an estimated 477 new COPD diagnoses, significantly reducing the undiagnosed COPD prevalence by 0.2% (p<0.05). Compared to the same period in 2009, referrals to PR increased from 78 to 119 (52%) in the first 6/12. Audits of oxygen therapy identified ongoing unnecessary payment in 52 patients (47 died/moved, five patients no longer required oxygen). Twenty-nine patients on LTOT had not been reviewed and were subsequently referred. The LES impact on the rate of emergency admissions for COPD remains unclear. Conclusions: One year evaluation demonstrates the COPD-LES is an effective strategy to improve case finding and diagnosis of COPD, improve PR referrals and rationalise oxygen prescribing. Ongoing audit of COPD emergency admissions will determine whether the LES achieves its objective.